The perspectives of pharmacological correction of depressive disorders and cognitive deficit as post-traumatic epilepsy leading syndromes - Ostapenko, I. (Journal of Education, Health and Sport, 2022)
Traumatic brain injury is the leading cause of symptomatic epilepsy at a young age. Post-traumatic epilepsy (PTE) is the main factor in disabling patients of working age and impairs the quality of life. Comorbid pathology in the form of psychoemotional and cognitive disorders essentially has a single pathogenetic mechanism on the part of traumatic brain disease. There are problems with differential diagnosis between comorbid and direct manifestations of PTE. The above dictates the need to develop modern complex approaches to the treatment of PTE and correction of accompanying and comorbid pathological conditions. Author tries to develop new pathogenetically adequate approaches to the treatment of PTE with correction of the psycho-emotional sphere and cognitive deficit. 44 patients with PTE were examined. The average period of its formation reached 10.3±4.2 years, and the frequency of attacks – 2.4±0.9 per month. Focal attacks prevailed (61.4%). In addition to standard long-term anticonvulsant monotherapy, the main group (32 patients) was prescribed ethylmethylhydroxyperidine succinate and vortioxetine. The control group (12 patients) received only anticonvulsant therapy. When using the proposed complex treatment, the number of people with depression decreased from 25 (56.8%) to 10 (22.7%) cases, that is, by 2.5 times (P <0.05). In the main group, from 59.4% to 21.9%, i.e. 2.7 times (Р<0.05). In the control – from 50.0% to 41.7% (Р>0.05). 37.5% registered positive dynamics in relation to pathological activity on the electroencephalogram. According to the Luria A. R. test, the average values of the obtained data at all stages of word presentation were probably higher than at the beginning of the study. Indicators of long-term memory changed similarly. Thus, the proposed treatment approach has a beneficial effect on the main pathogenetic links of the development of PTE, its course and corrects cognitive deficits, psychoemotional layers, which are comorbid conditions.